METODE PEMBELAJARAN YANG EFEKTIF DI SEKOLAH DASAR NEGERI 3 SIALANG PASUNG - Natasya Nurul Adha; Neli Selvira; Rezkiah; Silsi Anggi Septiana; Dea Mustika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Lecture, discussion, and assignment methods are effective learning processes in increasing student learning activity. In this process, teachers not only ensure that students acquire knowledge, but also ensure that students learn to communicate, collaborate, and respect the opinions of others. This study used a qualitative research method. The results showed that the learning methods used at Sialang Pasung 3 Public Elementary School were enjoyable for students and helped improve their learning outcomes. By implementing these methods effectively, teachers can maximize students' potential in achieving the desired learning objectives.